2018
DOI: 10.1038/s41419-018-1181-x
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of radiation-induced bystander effects by agents that inactivate cell-free chromatin released from irradiated dying cells

Abstract: Radiation-induced bystander effect (RIBE) is a poorly understood phenomenon wherein non-targeted cells exhibit effects of radiation. We have reported that cell-free chromatin (cfCh) particles that are released from dying cells can integrate into genomes of surrounding healthy cells to induce DNA damage and inflammation. This raised the possibility that RIBE might be induced by cfCh released from irradiated dying cells. When conditioned media from BrdU-labeled irradiated cells were passed through filters of por… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
76
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(78 citation statements)
references
References 38 publications
0
76
0
2
Order By: Relevance
“…Studies on bystander responses suggest that bystander signals may be transferred to neighboring cells either by gap junctional intercellular communication or by the production of exosomes or soluble extracellular signaling factors released from stressed targeted cells [3,13,16,17]. Soluble extracellular signaling factors such as ROS, nitric oxide (NO), extracellular DNA, and cytokines including TGF-β have been found to play an important role in multiple stressor-induced bystander effects [37,38,39,40]. Cell viability was the main cell response regulated by the bystander effect veri ed by the inhibitors (Fig.…”
Section: Characteristics Of Ws 2 Nanosheetsmentioning
confidence: 99%
“…Studies on bystander responses suggest that bystander signals may be transferred to neighboring cells either by gap junctional intercellular communication or by the production of exosomes or soluble extracellular signaling factors released from stressed targeted cells [3,13,16,17]. Soluble extracellular signaling factors such as ROS, nitric oxide (NO), extracellular DNA, and cytokines including TGF-β have been found to play an important role in multiple stressor-induced bystander effects [37,38,39,40]. Cell viability was the main cell response regulated by the bystander effect veri ed by the inhibitors (Fig.…”
Section: Characteristics Of Ws 2 Nanosheetsmentioning
confidence: 99%
“…Studies ful filled by I. Mittra show that the new class of phys iological mobile genetic elements is nucleic acids released from both healthy and damaged (inclu ding cancer / irradiated) cells [50,51]. S. Kirolikar et al found that such non cellular chromatin (cfCh) particles released due to the apoptosis of Jurkat cells (human lymphoblastic leukemia) irra diated at 15,0 Gy were integrated into the genomes of surrounding intact mouse fibroblasts (NIH3T3 cells) and induced in them bystander effect (acti vation of H2AX, caspase 3, NFκB and IL 6) under joint incubation for 24 hours [52].…”
Section: Reviewsmentioning
confidence: 99%
“…В дослідженнях I. Mittra зі співавторами показано, що новим класом фізіоло гічних мобільних генетичних елементів є нуклеїнові кислоти, вивільнені як зі здорових, так і з пошкодже них (у тому числі, ракових чи опромінених) клітин [50,51]. S. Kirolikar з колегами встановлено, що безклітинні хроматинові (cfCh) частинки, вивільнені внаслідок апоптозу Jurkat клітинами (лімфобластної лейкемії людини), опроміненими в дозі 15,0 Гр, інтег рувались в геноми оточуючих інтактних фібробластів миші (NIH3T3 клітин) та індукували в них ефект свідка (активація H2AX, каспази 3, NFκB і IL 6 ) при спільній інкубації протягом 24 год [52].…”
Section: Reviewsunclassified
See 2 more Smart Citations